The effect of promotional mix on the increased sales of sports products - Mehdi Rastegari, Sead Hesam Bostani (Opción, 2019)
The paper aims to study the effect of promotional mix on the sale of athletic products in Shiraz city. The statistical population of this study consisted of all the consumers visiting stores selling sporting goods in Shiraz, the number of which is unlimited. Data were analyzed using the Structural Equation Model (SEM) via LISREL software. Results indicate that the effect of promotional mix and its dimension (i.e. advertisements, sale campaigns, public relations, personal sale) has a significant effect on the sale of sporting goods in Shiraz, and hence recommendations are offered for the industry in this regard.